PENGARUH EVENT, IKLAN DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK SHOPEE DI SEMARANG - Khafidhoh, Nully Huda Imam; Hartono, Budi (Transpublika Publisher, 2023)
Developments in this technological era have influenced manufacturers to innovate in promoting their products to consumers, such as promoting their products on the Shopee application. This research aims to analyze the magnitude of the influence of events, advertising and sales promotions on purchase decisions of Shopee consumers in Semarang. In this study, the researchers determined that the sample used was 100 Shopee consumers in Semarang and had at least made transactions at Shopee e-commerce. The analytical test used is an instrument test (validity and reliability), classic assumption test, hypothesis testing and multiple linear regression analysis. The results of this research indicate that variables such as events, advertisements, and sales promotions have a significant effect, either partially or simultaneously, on the purchasing decisions of Shopee consumers in Semarang.